2014
DOI: 10.1007/s40093-014-0077-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cow manure vermicompost and municipal solid waste compost on peppermint (Mentha piperita L.) in Torbat-e-Jam and Rasht regions of Iran

Abstract: Background The utilization of organic fertilizer is an effective method in organic culture of medicinal plants because of its beneficial effects on soil structure, reduction of environmental problem and improvement in plant growth. The experiments were conducted in a research field at the University of Guilan at the Rasht and Torbat-e-Jam Razavi Khorasan Province, Iran. The experiment was conducted to determine the effects of 7 Mt ha-1 of cow manure vermicompost, vermiwash prepared from 7 Mt ha-1 of vermicompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…Similarly residual effect of sewage sludge increased the P content of leaves by 83%. Ayyobi et al (2014) concluded that organic fertilizers beneficially affect soil structure and nutrient availability. The use of sustainable organic materials can increase fertility without negative effects on human health and environment.…”
Section: Wastewatermentioning
confidence: 99%
“…Similarly residual effect of sewage sludge increased the P content of leaves by 83%. Ayyobi et al (2014) concluded that organic fertilizers beneficially affect soil structure and nutrient availability. The use of sustainable organic materials can increase fertility without negative effects on human health and environment.…”
Section: Wastewatermentioning
confidence: 99%
“…Vermicompost can retain nutrients for a long time, and has a high water-holding capacity and high porosity compared to conventional compost due to its humus content [3]. At present, vermicompost has been widely used in the cultivation field, and its ability to produce good crop yields is well-known, as reported for maize [8], wheat [9], peppermint [10], and tomatoes [11]. The application of vermicompost yielded the same effect as in the case of inorganic fertilizers administration [12,13], therefore rendering vermicompost as a good alternative to replace the application of chemical fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high cost and the harmful impact of inorganic fertilizers, using organic material is developing. The use of organic sources ameliorates soil structure and increase nutrient availability by sustaining the balance of organic matter, thereby helping to improve physical, chemical, and biological properties of the soil [8], [9] Vermicompost, which is organic wastes digested by earthworms, contains nutrients in a form that is easily absorbed by the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Vermicompost has a very positive influence on soil and plant [7]. Previous reports have shown that vermicompost moderates the detrimental effects of salinity stress on several crops [9][10][11][12][13][14][15][16]. Silicon (Si) is the second most abundant element in soils; it is mostly inert and only slightly soluble.…”
Section: Introductionmentioning
confidence: 99%